The interplay of psychedelic use and meditation in shaping psychological well-being - Krabbe, Andreas; Sikka, Pilleriin; Jylkkä, Jussi (Academic Press, 2026)
Psychedelic substances and meditation can elicit personally meaningful experiences that support well-being, yet their relative and combined contributions remain unclear. Meditation typically produces gradual improvements through sustained practice, whereas psychedelics may induce acute shifts. To examine these dynamics, we re-analysed data from two cross-sectional online surveys using multiple regression models. In Study 1 (N = 679), we assessed associations of cumulative psychedelic use and meditation practice with well-being, ill-being, and psychological flexibility. When examined separately, both practices were associated with greater well-being and flexibility. However, when considered jointly, the associations for psychedelics were reduced or became nonsignificant, whereas meditation remained consistently associated with the outcomes. Weak evidence also emerged for a potential synergy effect via an interaction between the two practices. In Study 2 (N = 137), we examined perceived well-being changes following a personally meaningful experience facilitated by psychedelics alone, meditation alone, or both combined. Participants in the combined and meditation groups reported significantly greater improvements compared with the psychedelic-only group, although all groups showed positive change on average. Together, these findings suggest that meditation may enhance the benefits of psychedelic experiences and that meditation practice can confound associations between psychedelic use and well-being. More broadly, they highlight the importance of considering both practices together when evaluating their contributions to mental health outcomes.